PERIODS OF THE DEVELOPMENT PSYCHOLOGY OF TEACHING FOREIGN LANGUAGES - Toshboyeva B.O (University Research Base, 2024)
This article is devoted to the issues of periodization of the psychology of teaching foreign languages. The psychology of teaching foreign languages is directly related to educational psychology because it seems necessary to us to consider approaches to its periodization with the periodization of the development of educational psychology, which are the most famous.